PENGUNGKAPAN NON FINANCIAL MEASURES: PENILAIAN VALUE RELEVANCE BAGI INVESTOR DAN PENGARUHNYA TERHADAP COST OF EQUITY DAN PERFORMANCE BAGI PERUSAHAAN PUBLIK - Wondabio, Ludovicus Sensi (Jurnal Akuntansi dan Keuangan Indonesia, 2007)
Research has called for increased demand of non financial measures (NFM) disclosure. This research examines the association between firm characteristics and the extent of NFM disclosure. Furthermore, we investigate the value relevance of NFM disclosure and its effects to cost of equity andfirms performance. The results of this research are: (1) firm strategy (prospector/ defender), regulatory factors, firms ’ age and foreign ownership are significantly positively associated with the level of NFM disclosure (2) NFM disclosure is a good signal for investors, which is relevant for earning persistency valuation. (3) the level of NFM disclosure is significantly negatively associated with cost ofequity (4) the level of NFM disclosure is significantly positively associated with firm performance.